HUMANIZATION AND ART: THE IMPORTANCE OF PLAYFULNESS FOR INSTITUTIONALIZED CHILDREN - Azarias , Késsia Giovanna Bresque; Ferraz, Marcela Aparecida Alvarez; Waner , Carolina Godoy; de Oliveira , Ariane Corda; Ribeiro, Ingrid Aparecida de Lima; Xavier, Raiane Piccioni; Giordani , Annecy Tojeiro; Borges , Tatiane Angélica Phelipini (Seven Editora, 2024)
Institutionalized children are those removed from their family environments, for some reason, and are inserted in institutions, popularly known as "homes/shelters", to experience the process of family reintegration, or for the adoption process, carrying with them marks and complex experiences since childhood, due to the fact that they are removed from their homes due to situations of abandonment,  mistreatment, negligence, exploitation, among many other possible causes. Thus, playful activities and art can and should be considered indispensable for the reception, development and learning inherent and healthy, aiming at awakening the possibility of creating and recreating through perception, imagination, feelings and the very fantasy built by the child who communicates with himself and with the world, starting to accept the existence of others,  the establishment of rules in their social relations, building knowledge and developing integrally. Thus, this extension project aimed to carry out humanization and care actions intertwined with art, divided into four fronts of action (clowning, storytelling, music and handicrafts), and to promote playful care practices through art with these four fronts. In this sense, the actions carried out through play provide these children with the ability to develop their individuality and integrality through activities that, intertwined with art, encompass cognitive development, affectivity, communication, interaction and socialization, thus creating the establishment of moral and value judgment, as they will be able to explore the environment around them,  their imagination, their feelings, their creativity and their ability to interact and socialize. Thus, it was evidenced that there are numerous strategies that can be combined with care and assistance and welcoming, in order to move away from the trend of dehumanized care strongly associated with "shelters". DOI:https://doi.org/10.56238/sevened2024.037-014